The Effect of Laser Treatment of WC-Co Coatings on Their Failure under Thermal Cycling; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Kasterov A. Artur; Shugurov A. Artur; Kazachenok M. Marina; Panin A. V. Alexey Viktorovich; Chin-Hsiang Cheng; I-Ling Chang (2016, 2016)
Title screen